The association between resilience and diabetic neuropathy by socioeconomic position: Cross-sectional findings from the KORA-Age study - Perna, Laura; Mielck, Andreas; Lacruz, Maria E; Emeny, Rebecca T; von Eisenhart Rothe, Alexander; Meisinger, Christa; Ladwig, Karl-Heinz (Journal of health psychology, 2015)
We investigated whether older adults with diabetes mellitus and lower resilience have an increased risk of diabetic neuropathy as compared to older adults with higher resilience, and whether this association varies by socioeconomic position. In total, 3942 individuals took part in a health survey in Augsburg, Germany, in 2008–2010 (KORA-Age study). We found that among participants with low socioeconomic position, those with higher resilience had a lower probability of suffering from neuropathy as compared to participants with lower resilience (absolute risk reduction = 10%). Adjusted odds ratio with 95% confidence intervals for the outcome diabetic neuropathy also showed that lower resilience scores had an independent effect in increasing the risk of diabetic neuropathy among elderly individuals with a low socioeconomic position (odds ratio: 1.83; confidence interval: 1.09–3.08). Health-promoting strategies focussing on resilience should be further explored.